Histopathology and immunohistochemistry assessments of acute experimental infection by Brucella melitensis in bucks - Nasruddin, Nurrul Shaqinah; Mazlan, Mazlina; Saad, Mohd Zamri; Hamzah, Hazilawati; Sabri, Jasni (Scientific Research Publishing, 2014)
Brucellosis in male goats is characterized by arthritis, orchitis and epididymitis, which may induce infertility. Nevertheless, these lesions were categorized as chronic while acute lesions had not been described. This study investigates the histopathological and immuno histochemistry reactions in organs of bucks acutely infected by Brucella melitensis. Results: Only testis and prepuce of acutely infected bucks showed significantly severe histological lesions. Other internal organs had mild to moderate lesions. However, positive immunohistochemistry stainings were observed in organs except the bulbourethral gland. There was a significant positive correlation between the distribution of B. melitensis and IHC intensity but no significant correlation between the IHC intensity and histopathology lesions. Conclusion: The results indicate that acute brucellosis did not lead to clinical presentation, although B. melitensis was well distributed in various organs of bucks.